The Effect of a Consumption-Based Accounting Method in National GHG Inventories: A Trilateral Trade System Application - Bastianoni, Simone; Caro, Dario; Borghesi, Simone; Pulselli, Federico Maria (Frontiers in Energy Research, 2014)
The allocation of emissions embodied in international trade is crucial to evaluate the real impact of countries in the climate change and their responsibility in greenhouse gas emissions. In this paper we apply a new theoretical framework that allocates the emissions embodied in international trade and computes the consequent carbon transferred across countries, according to a consumption-based accounting. The method uses the value of goods traded internationally and the respective carbon intensity as a average national emissions coefficient.. We analyze a trilateral trade system composed by Sweden, Italy and Poland during the period 2000-2008. We find that, with respect to the conventional greenhouse gas national inventory schemes, consumption-based accounting implies an increase of Italian and Swedish emission responsibility by 1.4% and 11.8%, respectively, and a decrease of Polish one by 2.81%. We also assess the relevance of this framework at the sectoral level by hypothesizing a shift of Italian imports of Machinery and Transport Equipment from Poland to Sweden. We deduce that, through appropriate policies, importer nations could be encouraged to find producers with the best environmental performances while exporter nations could be induced to reduce their carbon intensity to stimulate the international demand for their goods. Finally, we discuss some policy implications deriving from the application of the consumption-based accounting. The analysis performed in the paper suggests that the consumption-based accounting could be an important tool in the climate change challenge to reduce global emissions.